Psychoimmunology: a questionable model? - Vuitton, D A; de Wazières, B; Dupond, J L (La revue de medecine interne, 1999)
The concept of "psychoimmunology" that had long been supported by clinical observation and common sense, has acquired a sound scientific basis in the last two decades. The discovery of neuro-mediators and cytokines and their receptors shared by the central nervous system and the immune system has prompted research work using reliable methodologies to study the relationship between a 'hard' scientific field, such as immunology, and a 'soft' one, such as the behavioral sciences. The complexity of the studies on stress and immunity lies upon the choice of immunological measurements and the development of reproducible stress protocols. Models of stress in experimental animals may address acute versus chronic stress, and individual versus social stress. In humans, typical situations such as academic exams, and care given to patients with dementia, for instance, have been chosen to study large groups of subjects. The development of self-questionnaires for a reliable evaluation of stress and its consequences has led to more accurate measurements of psychosocial events. In animals, acute stress usually drives the immune response towards a Th2, grossly 'immunosuppressive,' profile. In humans, acute stress associates an endocrine response (characterized by glucocorticoid secretion and hyperprolectinemia) with an immunosuppression. Chronic stress is more likely to induce a range of effects, depending on the capacity of the subject to cope with stress, and on his/her social environment. Among the numerous mediators of the hypothalamo-pituitary cascade, Corticotropin Releasing Hormone is a key factor in the stress-immunity relationship. Several studies in humans have demonstrated the influence of stress on the susceptibility to infections (including HIV infection) and on survival in malignant diseases. In autoimmune diseases, a high prevalence of depression, as well as a particular sensitivity to stressful events, seem to modify the course of conditions such as systemic lupus erythematosus, rhumatoid arthritis or Sjögren's disease. The relationship between stress and diseases is based on the pathogenic model which involves the following chain of events: stressor, reaction to stress, neuro-endocrine changes, abnormalities of the immune response, and occurrence (or aggravation) of a disease. The evolution from health to disease could be associated, at least partially, with a 'passive' immunosuppressive mode of response, mediated by the pituitary-adrenal axis, typically the opposite of an 'active,' immunostimulant mode of response, mediated by adrenergic stimulation. Concept-related problems still remain to be solved: adaptation to stress ('coping'), is both genetically and socially mediated; the significance and interpretation of stress-related abnormalities and their precise involvement in the pathogenesis of diseases may be ambiguous. However, available epidemiological and pathophysiological evidence is currently sufficient to allow physicians in their everyday practice to take stress and depression into account in order to markedly improve the prognosis of many diseases related to immune responses. Prospective studies of neuropsychological intervention, using either pharmacologic or behavioral approaches, should be made to provide the necessary rational to a psychoimmunological management of patients.